ORGANIZATIONAL CULTURE AND WORK ETHIC ON EMPLOYEE PERFORMANCE IN HIGHER EDUCATION ENVIRONMENT - Fransiskus Nendi; Fransikus Jemadi; Benediktus Feliks Hatam (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
The performance of educational staff is a strategic factor in determining the quality of services and the image of higher education institutions; however, it has not yet reached its full potential due to the weak internalization of organizational culture and work ethic. This study aims to analyze the influence of organizational culture and work ethic, both partially and simultaneously, on the performance of educational staff. The study used an ex post facto design with a population of 66 respondents, all sampled using a saturated sampling technique. Data collection was conducted using a Likert-scale questionnaire. Data analysis utilized simple regression, multiple regression, and partial correlation. The results indicate that organizational culture has a positive and significant effect on the performance of educational staff, and similarly, work ethic has a positive and significant effect on performance. Simultaneously, organizational culture and work ethic were found to have a positive, significant effect on the performance of educational staff. These findings confirm that consistent internalization of organizational culture can foster a constructive work ethic and improve professional work behavior. Thus, organizational culture and work ethic are key determinants of educational staff performance. This study contributes to enriching empirical research on human resource management in higher education and offers practical implications for strengthening policies.